Meteorological variables and soil moisture in the detachment force coffee fruit - da Silva, Flávio Castro; da Silva, Fábio Moreira; Sales, Ronan Souza; Ferraz, Gabriel Araújo e Silva; de Barros, Murilo Machado (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to identify whether climatic and soil moisture variables are related with the variation of detachment force coffee fruits (Coffea arabica L.) during the crop harvest period. The research was carried out at Departamento de Agricultura at Universidade Federal de Lavras (UFLA) trying to analyze the behavior of detachment force coffee fruits in green and cherry maturation throughout the crop harvest period by the meteorological variables air and soil moisture, driving tests under four different soil moisture conditioning. Changes in meteorological parameters and soil moisture cause the change of the detachment force fruit, especially in green maturity. With increasing temperature was decreased of force of the green fruit and reduced tendency for cherry fruit. Soil moisture was positively correlated with the detachment force green fruits and positive trend for fruit cherry. Precipitation tends to decrease the detachment force of green and cherry fruit in the three days after its occurrence.